Pengaruh Gaya Mengajar Guru dan Motivasi Terhadap Hasil Belajar Siswa Akidah Akhlak MAN 3 Jakarta - Dwi AssyifahRiani (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
This study aims to determine the influence of variations in teacher teaching styles on student learning motivation and learning outcomes. The method in this study used an quantitative method with the sample model used, namely 133 students of grade X at MAN 3 Jakarta. Data collection uses questionnaire and interview instruments compiled based on theoretical reference indicators. The results of the study show that: 1) There is a positive and significant influence of teacher teaching style on learning outcomes, indicated by (rx1y) of 0.290 and r square of 0.084; 2) There is a positive and significant influence of learning motivation on learning outcomes, indicated by (rx1y) of 0.716 and r square of 0.512; and 3) There is a positive and significant influence of teacher teaching style and motivation on learning outcomes of class X students at MAN 3 Jakarta. Contributions for positive diagram values on teaching style are 67%, learning motivation is 66% and learning outcomes are 52%. Thus, it means that the influence of the teacher's teaching style and motivation variables on learning outcomes is 51.0%. While the remaining 49% is influenced by other variables not included in this model.